2010
DOI: 10.1097/mrr.0b013e32832e6b37
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of physical performance and objective fatigability in people with mild-to-moderate traumatic brain injury

Abstract: The aims of this study were to objectively measure the physical performance and physical endurance of patients with traumatic brain injury with minimization of cognitive and psychological fatigue, and to compare the physical performance of brain injured patients with that of healthy controls. This was a nonrandomized partially blinded controlled study. The study setting was the Outpatient Multidisciplinary Brain Injury Clinic in the Department of Physical Medicine and Rehabilitation of a tertiary care universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The literature contains discrepancies regarding the perceived exertion reported by participants with and without brain injury. [33][34][35] Similar to our findings, Dawes et al 34 reported that individuals with brain injury had shorter exercise tests; however, they found no differences in ratings of exertion. This inconsistency may be due to differences in brain injury between studies because Dawes et al 34 evaluated participants with TBI and stroke.…”
Section: Ratings Of Perceived Exertionsupporting
confidence: 91%
“…The literature contains discrepancies regarding the perceived exertion reported by participants with and without brain injury. [33][34][35] Similar to our findings, Dawes et al 34 reported that individuals with brain injury had shorter exercise tests; however, they found no differences in ratings of exertion. This inconsistency may be due to differences in brain injury between studies because Dawes et al 34 evaluated participants with TBI and stroke.…”
Section: Ratings Of Perceived Exertionsupporting
confidence: 91%
“…However, this may be due to poor study design and/or poorly defined fatigue outcome measures. For example, the Six-Minute Walk Test was found to be a useful instrument in segregating physical fatigue from cognitive and psychological aspects of fatigue [119], but this test has not been consistently used to asses fatigue in studies of physical activity. More recently, vigorous aerobic exercise training has been shown to reduce physical fatigue in some individuals with TBI [120].…”
Section: Treatmentmentioning
confidence: 99%
“…The experience of PTBIF can be both physical and cognitive (Elovic et al, 2005;Levine & Greenwald, 2009;Merritta, Cherian, Macaden, & John, 2010;Olver et al, 1996). It is often associated with a felt sense of disproportionate exertion and associated mental or physical exhaustion and inability to perform.…”
Section: Epidemiology and Characteristicsmentioning
confidence: 99%
“…There is limited evidence linking physical performance and self-reported fatigue in individuals with TBI (Merritta et al, 2010). Furthermore, there is little relationship between self-reported fatigue and frequency of participation in diverse daily activities such as work, family, recreation, etc (Bushnik, Englander, & Wright, 2008a;Cantor et al, 2008).…”
Section: Measurement Of Ptbifmentioning
confidence: 99%